Pengaruh Pelatihan Komunikasi Efektif Petugas Informasi dan Pendaftaran terhadap Kepuasan Pasien Rawat Jalan - Wardani, Ika Kusuma; Sarwiyata, Tri Wahyu; Koeswo, Mulyatim (Judika (Jurnal Nusantara Medika), 2017)
One of the causes of the decline in outpatient visits at the Islamic Hospital of Malang is the limited communication of information and registration officers. Information that is poorly understood by the patient raises a different perception and. This study is intended to determine the effect of effective communication training of information and registration officers on patient satisfaction as measured from the level of patient satisfaction. This study is an experimental quasi-research. The sample size used is 61 people through purposive sampling technique. Result of statistic test using Wilcoxon Signed Rank Test which increase patient satisfaction based on Z count = - 4.777 with α = 0,05 and sig value. 0.012 <p value of 0.05.